Pengaruh Infrared Dan Cailliet Exercise Terhadap Penurunan Nyeri Dan Spasme Otot Pada Pasien Spondylosis Cervikal Di Rumkit Tk Iv 01.07.01 Pematangsiantar - Devi Juraidah; Maryaningsih Maryaningsih; Sulaiman Sulaiman (Jurnal Kesehatan dan Fisioterapi, 2023)
Background: This study aims to find out the influence of infrared and cailliet exercise on decreased muscle pain and spasm in cervical spondylosis patients. Research Methods: The population in this study was 50 patients and according to the calculation of the results of the sample in this study were 17 people, who were patients. The hypothesis given in this study is that there is an infrared and cailliet exercise effect on decreased muscle pain and spasm in cervical spondylosis patients. Discussion: The hypothesis given in this study is that there is an infrared and cailliet exercise effect on decreased muscle pain and spasm in cervical spondylosis patients. Assuming the higher the infrared and neck cailliet exercise, the less neck pain and muscle spasms in cervical spondylosis patients. Data collection is carried out using Quasi experimental with the design of One Group Pretest-Posttest Design. Sampling technique using purposive sampling and determination of sample number using Slovin formula with a critical value of 20%. Data analysis uses bivariate analysis with the wilcoxon signed test method. Results: Based on the data, it was obtained that there was a meaningful influence on the difference given to each variable with a significant p = 0.000 < 0.050. Conclusion: This means that the hypothesis proposed the higher the administration of Infrared and cailliet exercise, the less neck pain and muscle spasm in cervical spondylosis patients are declared accepted.Keywords: Infrared, Caiiliet Exercise, Spondylosis.